The State Results-Based Management System of Minas Gerais, Brazil - Busjeet, Gita (World Bank, Washington, DC, 2012)
In 2003, Minas Gerais's state government (GMG) launched an ambitious plan that gradually introduced a results focus into the public administration and led to the creation of a Results-Based Management (RBM) system relying on performance information generated by Monitoring and Evaluation (M&E) tools. A case study of Minas Gerais's RBM system offers insights on: 1) the role of a facilitating environment and individual government champions for reform; 2) M&E tools founded on the desire to strengthen strategic planning; 3) the power of a strong incentive structure; and 4) the value added of investment in institutional and human capacities. The focus on priority policy areas and programs allowed GMG to build an RBM system supported by M&E infrastructure led by the executive branches of government: the governor and vice governor, the Ministry of Planning and Management (SEPLAG) and the State for Results Program (EpR), a small executive team created in 2007 specifically to provide support to the states for results reform agenda.